Manajemen Produksi Variety Show dan Sinetron dalam Memenuhi Kepentingan Publik - Intan Ikhtiarti Wilti; Harmonis Harmonis (Persepsi: Communication Journal, 2022)
AbstractTelevision stations compete in packaging an event through creativity in order to win the competition and attract the attention of the audience. In the implementation of broadcasting activities, a broadcasting institution requires expertise in the field of management, namely broadcasting management. Variety Show programs that air on television provide entertainment and are able to attract the hearts of viewers. Soap operas form an amalgamation and shortening of cinema and electronics. Television soap opera packages are one form of educating people to behave in harmony with the order of cultural norms and values. Automatically, the message content that is seen symbolically in the soap opera package is in the form of social criticism and social control about deviations that are currently in the community. The purpose of this study was to determine the production management process of variety shows and soap operas on television. This research uses media management theory. This research method is qualitative and this type of research is descriptive. Research data collection techniques using interview techniques. The result is that the two informants gave their opinions and assessments regarding the current variety shows and soap operas on television. They said that there were several variety shows and soap operas that did not actually fulfill the public's interest.Keywords: Media Management, Broadcast Media